Optimization of Surface Roughness and Material Removal Rate in Turning of Al-6061 Using Taguchi Methodology, Fuzzy Logic, and Measurement System Analysis - Manoj S. Lohate; Sagar B. Kadu; Pravin T. Nitnaware; Vedanti Bhoge; Aniket Shinde; Kaustubh Tattapure; Abhishek Gawali (International Journal of Machine Systems and Manufacturing Technology, 2026)
The optimization of machining parameters please a crucial role in improving product quality and productivity in manufacturing processes. This study focuses on the turning of aluminium 6061 alloy, aiming to optimize two key performance measures: Surface Roughness and Material Removal Rate. An integrated approach combining to Taguchi methodology, fuzzy logic and measurement system analysis (MSA) is proposed to achieve this objective. Taguchi design of experiments using and L9 orthogonal array has helped to get the effects on process parameters – speed, cutting depth and feed rate– on the selected responses. Fuzzy logic is utilized to change the multi response problem into a one performance index facility simultaneous optimization of Ra and MRR. Additionally, MSA is conducted using gauge repeatability and reproducibility into bracket are and are bracket closed to ensure the reliability of the measured data. The analysis reveals that the chosen methodology effectively identifies optimal parameter settings resulting in improved surface quality and machining efficiency.
Keywords: MRR; Measurement System Analysis (MSA); Optimization; Ra; Taguchi-Fuzzy hybrid approach; Turning Process